ضغوط العمل لدى معلمي المدارس الابتدائية وعلاقتها بمركز الضبط (Journal Of Educational and Psychological Researches, 2011)
Human exposure in the course of his life to a series of pressures that are problems or difficulties Human faces and objects to the way and hinder it from continuing and require resolution or removed from the way Problems may appear suddenly or difficulties may have warning signs of preparing a human May be simple or complex and may come apart or the ripples of it, and that the most important factors that Lead to the creation of pressure is not to satisfy the basic needs and the private ones.The importance of research in that the teacher is a fundamental pillar in the educational process and the success and failure of these Process depends mainly. Accordingly, the present study aimed to know the status of the pressures of work relationship with the teachers of the settings Primary schools, and to achieve objectives of the research the researcher calculates the validity and reliability The discriminatory power and Altaúa test and Pearson's correlation coefficient and analysis of variance unilateral  And test for a posteriori comparisons of the sample by 200 teachers from Primary schools of the city of Baghdad, after calculating the appropriate means to achieve research The following results:1 - Most of the teachers of the males and females have the pressure    of work. 2 - Most of the teachers of the males and females have external control center. 3 - there is a relationship between work stress and control center outside the primary school teachers. 4 - There are no differences in the pressures of work by training courses. 5 - There are no differences in the pressures of work by length of service. 6 - There are differences in the control center and in favor of males. 7 - There are no differences in the control center by training courses. 8 - There are no differences in the control center by years of service. The researcher recommended that officials at the Ministry of Education and the directorates of Education and school administrations Using modern educational methods in teaching, training courses .For all the different disciplines and for both sexes of male and female} {and enrich the libraries School primary school publications diversified and video to highlight the role of rights in The possibility of life and how to control and modify his behavior toward a better life. There are some suggestions given by a researcher for a study to determine the pressures of work And their relationship to the location of internal control. And conduct a study to determine the pressures of work and its relationship to parental treatment methods. And a Study to determine the pressures of work and its relationship to the achievement motivated managers of primary schools.